Interface-coupling of CoFe-LDH on MXene as high-performance oxygen evolution catalyst. (June 2019) - Hao, Chongyan; Wu, Yang; An, Yajing; Cui, Baihua; Lin, Jiannan; Li, Xiaoning; Wang, Dianhui; Jiang, Minhong; Cheng, Zhenxiang; Hu, Shi
Abstract: Oxygen evolution reaction (OER) is the bottleneck reaction of the overall water splitting process despite the intensive research in the past decades. Efficient yet stable low-cost OER catalysts have been widely explored but further improvement is still highly demanded. Herein, a type of hybrid OER catalyst was prepared by the growth of CoFe-LDH (layered double hydroxide) on the surface of Ti3 C2 MXene nanosheets, which exhibits superior OER performance than the state-of-the-art RuO2 . The enhancement of the OER performance could be attributed to the combination of oxygen-breaking ability of CoFe-LDH and metallic conductivity of Ti3 C2 MXene substrate. Meanwhile, the direct growth of CoFe-LDH on the hydroxyl-rich surface of MXene effectively prevents itself from aggregation, exposing more CoFe-LDH edge active sites. What's more important is that the intimate interface between CoFe-LDH and Ti3 C2 MXene brings in efficient charge transfer and oxygen activation, which is supported by the DFT calculation results. The direct growth of CoFe-LDH on MXene endows the insulating LDH with metallic features with the O 2p states become distributed above the Fermi level which is mediated by the possible anionic redox process. This work demonstrates the great potential of MXene-based hybrid nanostructure for energy conversion applications. Graphical abstract: Image 1 Highlights: Nanohybrid electrocatalyst of Ti3 C2 -MXene and CoFe-LDH is fabricated and characterized. Enhanced oxygen evolution performance is demonstrated in the LDH-MXene nanohybrid. Spectroscopy and DFT calculation are combined to understand the interfacial charge transfer and performance boost.